Crossroads and Intersections in the Post-Physical Archival Landscape: A Case Study at Middle Tennessee State University. Issue 4 (December 2016) - Knowles, Susan W.
This article traces the development of Southern Places, an online digital collection developed by Middle Tennessee State University's Center for Historic Preservation (CHP) and the James E. Walker Library for the purpose of creating a digital presence for the Center's work over the past thirty years. After outlining previous digitization projects undertaken by the CHP in partnership with the Walker Library and other institutions, attention is paid to the technical decisions made in terms of the selection of a content management system and Web hosting, metadata protocols, and the place of shared authority in the contemporary, post-physical archival landscape. The article also describes recent digitization and access efforts at Middle Tennessee State University and partnerships with other universities, libraries, and archives across the state.